Antigua and Barbuda : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1995)
This paper describes economic developments in Antigua and Barbuda during the 1990s. The growth of real GDP picked up to about 4 percent in 1993-94 on the strength of increased tourism while inflation remained low. The current account deficit of the public sector widened from less than 3 percent of GDP in 1990 to 4 percent of GDP in 1994, and the overall deficit went up to 6 1\2 percent of GDP. Public investment remained too low to provide for the upgrading of infrastructure needed for the continued growth of tourism and the economy.